Grizzly bear spiritual power and Shamanism in native cultures of the Pacific Slope of North America. - Comeau, Bernard G. (University of Ottawa (Canada), 1996)
The dissertation is a monograph of grizzly bear spiritual power as it was historically conceptualized and manifest among Native cultures of the Pacific Slope of North America. Focusing specifically upon cultural reports of persons (e.g., shamans) acknowledged to hold grizzly bear spiritual power, descriptive summaries outline the varied behaviours, abilities, and functions associated with these individuals, as well as the more general mythological themes, rituals, and ceremonies which reflected societal attitudes toward grizzly bears and grizzly bear spiritual power. Based on data from these summaries, correlational and factor analyses are employed to discern specific trends in the reported existences of "grizzly bear persons" as they were acknowledged among Pacific Slope cultures. Analyses yield four distinct types of grizzly bear persons. These types, according to their reported behaviours and functions, are named "grizzly bear sorcerer", "grizzly bear shaman-sorcerer", "grizzly bear shaman-healer", and "grizzly bear dancer". Subsequent correlational analyses show that trends in the existences of these types of grizzly bear persons are consistent with the cultural positions of the societies in which they were reported. The developed world-view of each culture was significant in determining both the particular conceptualizations and manifestations of grizzly bear spiritual power and the acknowledged existences, behaviours, and functions of grizzly bear persons. From these results, it is argued that grizzly bear spiritual power and grizzly bear persons were not unidimensional across Pacific Slope Native cultures. In noting the cultural specificity of the reported existences of grizzly bear shamans, current academic categorizations of shamanism are called into question. A model which highlights the inter-cultural and intra-cultural diversity of shamanism is advocated. Finally, conclusions are drawn with respect to the implications of this study for a more comprehensive understanding of spiritual power as it was expressed and manifest among North American Native cultures.
Keywords: Religion, General.